DEVELOPMENT OF WEB-BASED HEAT EQUATION MODEL WITH NUMERICAL SOLUTIONS - Puspa Rosanti, Yerika
Heat transfer is a common physical phenomenon in daily life, where the transfer of energy cannot be seen with the human eyes. The need for visualization on how temperature distribution occurs in a homogeneous material underlies this research. Interactive visualization can help study the dynamics of heat diffusion more effectively. This study aims to develop a numerical simulation of the onedimensional persamaan panas using the finite difference method and implement it on a web-based platform. The Forward Time Centered Space (FTCS) method is used to discretize the heat equation and solve it iteratively. The implementation is carried out using Javascript to allow the program to change the diffusivity parameters and length dimension of the material and observe their effects on the temperature distribution. The simulation results show how the temperature in a one-dimensional rod changes over time until it reaches a steady state, which can be observed from the real-time changing graph. Two types of boundary condition, Dirichlet and Neumann, are applied to evaluate their effects on the temperature distribution. With Dirichlet, the temperature at the ends of the rod is set to a fixed value, while Neumann set a fixed temperature gradient at the ends of the rod. By providing visual and interactive simulation for student, it can represent the abstract phenomena and support physics learning.